The Use of Innovative Pedagogical Technologies in Education is a Demand of the Times and Increasing the Quality of Education - Abdushukurova Zamira Zaynitdinovna; Umarova Dilnoza Alisher qizi (Zien Journals, 2023)
This article describes the essence of the use of innovative pedagogical technologies in education and its role and importance in improving the quality of education. Also, this article discusses the effectiveness of using innovative pedagogical technologies in the educational process and offers suggestions for a new approach to the educational process in higher education institutions
Keywords: innovation; pedagogical technology; quality of education